English and the Rest: Understanding the Languages of Science - Balan, Jorge (International Higher Education, 2011)
The increasing dominance of English in higher education and research over the last few decades is often assumed to be a linear, unavoidable, and cumulative process resulting in improved, perhaps more egalitarian, international academic communication worldwide. This article will offer some challenges regarding this view of a global trend in the adoption of English and discuss some dilemmas confronted by academics in developing countries where English is not the national lingua franca (i.e., outside the British Commonwealth countries).